Market Generic Strategy pada Usaha Warkop Angkringan Berbasis Internet (WiFi) di Kab Mojokerto - M. Syamsul Hidayat; Kasnowo; Tatas Ridho Nugroho (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2020)
The purpose of this research is to measure the Market Generic Strategy that is used by the owner of the internet (wifi) coffee shop / UMKM in Mojokerto Regency to be able to compete, be sustainable and achieve goals and get maximum profit. This research is an exploratory research that uses a qualitative approach in the form of a Focus Group Discussion. The sample consisted of 25 people, who were taken based on certain criteria. The technique of collecting data is by conducting open-ended interviews with the hope of obtaining complete information from these respondents. Data analysis using descriptive analysis method. The results showed that the Internet-based Market Generic Strategy of Warkop Angkringan (wifi) is a product differentiation strategy, service differentiation, personnel differentiation and focus strategy. Meanwhile, the way to retain customers is the availability of fast and friendly service, a variety of drinks and food, comfortable seating and room facilities as well as good cleanliness and layout.